The Influence of Profitability, Composition of the Independent Board of Commissioners and Managerial Ownership on Profit Management in Food and Beverage Companies on the Indonesian Stock Exchange Period 2017-2021 - Farida Sagala; Lamria Sagala; Kristanty MN Nadapdap; Bryan Carlos Gianri Siagian (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to identify and analyze the effect of profitability, independent board of commissioners composition and managerial ownership on earnings management. This study uses data analysis method using multiple linear regression analysis. Partial research results show that profitability has no effect and is not significant on earnings management. The composition of the independent board of commissioners also has no influence and is not significant on earnings management. Managerial ownership has no effect and is not significant on profitability.